Some Humanistic Motifs in the Lyrics of Vazha-Pshavela - Linda Tsitskishvili, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
In Georgian literary criticism Vazha-Pshavela's feel for nature, style, folk background etc. is widely spoken of. However less attention is paid to two humanistic problems which are represented in the lyrics of Vazha-Pshavela and presented in an original aspect at that. This time we will focus on the literary interpretation of death in the lyrics of the poet.